2021
DOI: 10.1007/s00125-021-05393-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linagliptin vs glimepiride on cognitive performance in type 2 diabetes: results of the randomised double-blind, active-controlled CAROLINA-COGNITION study

Abstract: Aims/hypothesis Type 2 diabetes, particularly with concomitant CVD, is associated with an increased risk of cognitive impairment. We assessed the effect on accelerated cognitive decline (ACD) of the DPP-4 inhibitor linagliptin vs the sulfonylurea glimepiride in individuals with type 2 diabetes. Methods The CAROLINA-COGNITION study was part of the randomised, double-blind, active-controlled CAROLINA trial that evaluated the cardiovascular safety of linaglip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
(63 reference statements)
1
33
0
Order By: Relevance
“…By reviewing existing clinical trial and/or MR studies of medication treatment and/or drug repurposing on Alzheimer’s disease, we found that cholinesterase inhibitors and NMDA receptor antagonist were the two most widely used anti-dementia medications 42,43 , which were recommended by the current National Institute for Health and Care Excellence (NICE) guidance for people with Alzheimer’s disease (https://www.nice.org.uk/guidance/cg42). We also found some evidence to support the role of liraglutide (one GLP-1 inhibitor) and most of the anti-hypertensive drugs on preventing/delaying cognitive impairment 37,38,39,40,41 . The level of prevention of liraglutide was similar to the effect estimate we observed on metformin targets (14%) 37 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…By reviewing existing clinical trial and/or MR studies of medication treatment and/or drug repurposing on Alzheimer’s disease, we found that cholinesterase inhibitors and NMDA receptor antagonist were the two most widely used anti-dementia medications 42,43 , which were recommended by the current National Institute for Health and Care Excellence (NICE) guidance for people with Alzheimer’s disease (https://www.nice.org.uk/guidance/cg42). We also found some evidence to support the role of liraglutide (one GLP-1 inhibitor) and most of the anti-hypertensive drugs on preventing/delaying cognitive impairment 37,38,39,40,41 . The level of prevention of liraglutide was similar to the effect estimate we observed on metformin targets (14%) 37 .…”
Section: Discussionsupporting
confidence: 53%
“…By reviewing existing clinical trial and/or MR studies of drug repurposing on Alzheimer's disease, we found some evidence to support the role of liraglutide (one GLP-1 inhibitor) and most of the anti-hypertensive drugs on preventing/delaying cognitive impairment 37,38,39,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence also supports the use of dipeptidyl peptidase-4 inhibitors or gliptins as potential drugs to prevent cognitive impairment through the preservation of Glucagon-like peptide 1 (GLP-1) function and increasing neurogenesis, among many other mechanisms [ 90 ]. However, the translation into clinical trials has failed, as has been shown recently [ 91 ]. In the CAROLINA-COGNITION study [ 91 ], 3163 diabetic participants (40 to 85 years old; HbA1c range of 48–69 mmol/mol (6.5–8.5%) and who received standard care, excluding insulin therapy) were randomized to linagliptin versus glimepiride and followed-up for a mean duration of 6.1 years.…”
Section: Resultsmentioning
confidence: 99%
“…However, the translation into clinical trials has failed, as has been shown recently [ 91 ]. In the CAROLINA-COGNITION study [ 91 ], 3163 diabetic participants (40 to 85 years old; HbA1c range of 48–69 mmol/mol (6.5–8.5%) and who received standard care, excluding insulin therapy) were randomized to linagliptin versus glimepiride and followed-up for a mean duration of 6.1 years. The study assessed the effect of linagliptin and glimepiride on accelerated cognitive decline in participants with a baseline MMSE score ≥24.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in a Bayesian network meta-analysis, the use of DPP-4 inhibitors was associated with a lower risk of dementia than no treatment with antidiabetic drugs, and DDP-4 inhibitors were the most effective antidiabetic drugs for dementia [ 19 ]. In contrast, two randomized controlled trials of linagliptin [ 78 , 79 ], a non-BBB-penetrating DPP-4 inhibitor, found no association between linagliptin use and maintenance of cognitive function. Unfortunately, there is no randomized controlled trial of BBB-penetrating DPP-4 inhibitors such as omarigliptin.…”
Section: Association Of Pharmacological and Pharmacokinetic Propertie...mentioning
confidence: 96%